2022
DOI: 10.1186/s12875-022-01837-1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal ankle-brachial index, cardiovascular risk factors and healthy lifestyle factors in hypertensive patients: prospective cohort study from a primary care urban population

Abstract: Background Peripheral arterial disease (PAD) and arterial stiffness (AS) may be hypertension-mediated vascular lesions. Both are determined by an abnormal ankle-brachial index (ABI) and are predictors of cardiovascular disease (CVD) and mortality. We assessed the relationship in urban hypertensive patients between an abnormal ABI and an ideal cardiovascular health (CVH) score, plus other healthy factors, with unfavourable outcomes. Methods We studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…A study by Emanuelsson et al showed that low ABIs may be associated with an increased risk of MI, even after adjusting for risk factors, which further promotes the use of the ABI as a risk assessment tool [ 28 ]. Multiple CVD risk factors are hypothesized to affect ABI [ 29 ]. In this study, we tested which risk factors had the greatest influence on the ABI.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Emanuelsson et al showed that low ABIs may be associated with an increased risk of MI, even after adjusting for risk factors, which further promotes the use of the ABI as a risk assessment tool [ 28 ]. Multiple CVD risk factors are hypothesized to affect ABI [ 29 ]. In this study, we tested which risk factors had the greatest influence on the ABI.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Emanuelsson et al showed that low ABIs may be associated with an increased risk of MI, even after adjusting for risk factors, which further promotes the use of the ABI as a risk assessment tool (26). Multiple CVD risk factors are hypothesized to affect ABI (27). In this study, we tested which risk factors had the greatest in uence on the ABI.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are diagnosed with PAD when their ABI values are ≤0.9 on either the left or right limb. [ 3 ] In terms of PAD categories, ABI values 0.7 to <0.90, 0.4 to <0.7, and <0.4 are considered mild, moderate, and severe PAD, respectively. When the ABI is between 0.91 and .99, it is considered borderline, and between 1.0 and 1.4 is considered normal, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…An ABI value >1.4 is an indication of the presence of stiff blood vessels, which is not considered PAD. [3][4][5]…”
Section: Pad Severity Measurementioning
confidence: 99%
See 1 more Smart Citation